2020
DOI: 10.1136/bjophthalmol-2020-316624
|View full text |Cite
|
Sign up to set email alerts
|

12-month randomised trial of 360° and 180° Schlemm’s canal incisions in suture trabeculotomy ab interno for open-angle glaucoma

Abstract: Background/AimsTo perform a 12-month comparison between the different extents and locations of Schlemm’s canal incisions during suture trabeculotomy ab interno for open-angle glaucoma (OAG).MethodsThis is a prospective, single-centre, three-arm randomised trial. A total of 99 eyes of 99 patients were randomly assigned to one of three groups: the 360° incision group (n=34), the upper-180° incision group (n=34) and the lower-180° incision group (n=31). Intraocular pressure (IOP), number of medications and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
4
50
0
Order By: Relevance
“…IOP reduction resulting from TM-targeted MIGS has been reported to occur approximately in the mid-teens regardless of the type of procedure 7 , 31 , 32 . Several reports have shown that the extent of incision or removal of the TM was not correlated with IOP reduction 32 35 , which was consistent with our results. However, a greater IOP reduction rate was significantly associated with higher preoperative IOP, which was also consistent with the results of previous studies 31 , 36 , 37 .…”
Section: Discussionsupporting
confidence: 93%
“…IOP reduction resulting from TM-targeted MIGS has been reported to occur approximately in the mid-teens regardless of the type of procedure 7 , 31 , 32 . Several reports have shown that the extent of incision or removal of the TM was not correlated with IOP reduction 32 35 , which was consistent with our results. However, a greater IOP reduction rate was significantly associated with higher preoperative IOP, which was also consistent with the results of previous studies 31 , 36 , 37 .…”
Section: Discussionsupporting
confidence: 93%
“…Manabe et al [ 11 ] examined increases in the extent of the incision in Schlemm’s canal to ≥150° and reported that this did not affect the reduction in the IOP at 1 year postoperatively. Sato et al [ 12 ] also showed that neither the 180° nor the 360° incision in Schlemm’s canal affected the IOP reduction. Furthermore, Mori et al [ 13 ] reported that there was no significant difference for the 1-year success rate between the 1- and 2-quadrant incisions in Schlemm’s canal when using μLOT.…”
Section: Discussionmentioning
confidence: 99%
“…However, opinions varied concerning the correlation between the extent of unroofed SC and IOP reduction. Some evidence supported that larger incisions contributed to a greater IOP lowering effect [ 16 , 40 ], while other voices argued that complete trabeculotomy did not provide additional outflow facility [ 41 , 42 ]. In practice, we noticed that the difficulty of suture cannulation differed from person to person, which presumably reflected the structural variations of SC.…”
Section: Discussionmentioning
confidence: 99%